COVID-Related Chronic Allograft Dysfunction in Lung Transplant Recipients: Long-Term Follow-up Results from Infections Occurring in the Pre-vaccination Era - René Hage; Macé M. Schuurmans (Transplantology, 2022)
Introduction: We report on characteristics and lung function outcomes among lung transplant recipients (LTRs) after COVID-19 with infections occurring in the first year of the coronavirus pandemic prior to introduction of the vaccines. Methods: This was a retrospective study of 18 LTRs who tested positive for SARS-CoV-2 between 1 February 2020 and 1 March 2021. The mean age was 49.9 (22–68) years; 12 patients (67%) were male. Two patients died due to severe COVID-19. Results: During the study period, there were 18 lung transplant recipients with a community-acquired SARS-CoV-2 infection. In this cohort, seven had mild, nine had moderate, and two had severe COVID-19. All patients with mild and moderate COVID-19 survived, but the two patients with severe COVID-19 died in the intensive care unit while intubated and on mechanical ventilation. Most patients with moderate COVID-19 showed a permanent lung function decrease that did not improve after 12 months. Conclusion: A majority of LTRs in the current cohort did not experience an alteration in the trajectory of FEV1 evolution after developing SARS-CoV-2 infection. However, in the patients with moderate COVID-19, most patients had a decline in the FEV1 that was present after 1 month after recovery and did not improve or even deteriorated further after 12 months. In LTRs, COVID-19 can have long-lasting effects on pulmonary function. Treatment strategies that influence this trajectory are needed.